Deepening financial inclusion through collaboration to create innovative and appropriate financial products for the poor - Tony K. Omwansa; Timothy Mwololo Waema (Kenya Bankers Association (KBA), 2014)
The Central Bank of Kenya has in the recent years introduced several regulatory interventions aimed at increasing financial inclusion. Mobile operators and financial institutions have successfully launched numerous services either to increase the convenience for existing customers or to reach out to new customers. There is evidence of more un-banked people moving into the formal financial grid and money initially circulating in informal systems can now be accounted for. Mobile money has made it much easier to receive and transfer money as well as make payments. Agency banking and cash merchants have taken the cash-incash-out points much closer to the consumers. Despite this progress, access to formal financial services in Kenya is still low. In particular, the very poor people who are characterised by low literacy levels and generally low, irregular and sporadic income, in most cases do not have the appropriate financial tools that fit their lifestyle and can help alleviate their poverty. Research shows that the poor need financial tools that are appropriate, flexible, convenient, quick and affordable. The mobile money channel and the agent network provide the best avenue so far for reaching the very poor, but the business case for serving this segment of the market has not been well developed to incentivise the main players to be actively involved. The findings in this paper are an amalgamation of three studies conducted in Kenya. The first study focused on developing case studies on how the prepaid and pay-as-you-go models riding on the rails of mobile money are being used to conveniently provide commodities and services to the very poor. The second study focused on the adoption drivers for mobile money at the base of the pyramid while the third evaluated the impact of pure mobile phone based micro-financing in Kenya. Building on literature about the poor and their money combined with evidence from the studies mentioned, the authors present practical and evidence-based recommendations to demonstrate that it takes additional players and innovative approaches to enable financial institutions and mobile network operators to develop and aggressively promote sophisticated financial services for the poor. The paper discusses key adoption drivers, lessons learnt about the characteristics and impact of new forms of financial services for the very poor. Design features for making financial services for the poor innovative and appropriate are discussed in the context of adoption drivers. The design features form a good basis for analysing the challenges of designing and deploying these products. Mobile money needs to be viewed more and more as a platform, as opposed to a product or service to be consumed. There is need for a deliberate effort to conduct multidisciplinary and all inclusive research and development on relevant products for thepoor that could be bundled with or ride on the rails of mobile money. Deploying and successfully managing services based on business models targeting the poor would require synergy between stakeholders, a vital ingredient that would facilitate financial inclusion and more broadly translate to benefits for the consumers.
Keywords: 330; mobile money; poor; financial inclusion